Use of Dashboards in Pharmaceutical Services: an integrative review - Barboza Arnaudin, Caroline; de Mendonça Lima, Tacio (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: A large volume of data generated in pharmaceutical services can make it difficult to visualize, interpret results, and decision-making. Dashboards are a useful tool in this process. Objective: To synthesize primary studies that described the use of dashboards in pharmaceutical services. Methodos: An integrative review was conducted through a literature search up to May 2024 in the Medline, Lilacs, Scopus databases, and the Google Scholar search engine (the first 60 records). The search strategy combi-ned keywords in English and/or Portuguese, including the following terms: ‘dashboards’, ‘pharmacist’, ‘pharmaceutical services’, and ‘pharmacy’. Results: The results were pre-sented in a narrative and tabular format. Nine studies were included in this review. Most of the studies were conducted in the United States, in the hospital pharmacy con-text and for logistic services. The studies demonstrated positive results from the use of dashboards for improving both the services provided to patients and the performance of pharmacists, although challenges have been identified, such as lack of data, insufficient professional training, and resistance to use. Conclusions: Therefore, although there are barriers to its implementation, the results indicate that the use of the tool should be en-couraged to support continuous improvement in the quality of pharmaceutical services.